Spelar tarmcellernas interna fettförbränning en roll i regleringen av födointag? - Ström, Gunilla (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2010)
Since several lifestyle diseases are associated with obesity much research is carried out within the area. Researchers have found that oxidation of fatty acids within the body’s cells may give rise to peripheral signals which regulate food intake, but it is still unclear where such a mechanism takes place. Although much evidence suggests that it is the hepatocytes in the liver that send signals regulating food intake, some researchers have begun to question this theory. Instead they argue that the mechanism takes place within the enterocytes since they are well localised in the gut for such assignment. Research has shown that the enterocytes can use fatty acids as an energy source and the oxidation may give rise to an afferent vagal signal to the brain stem where it is switched to the hypothalamus, causing a decrease in food intake. It has also been proved that there are afferent vagal nerve fibres in the gut mucosa, which theoretically could sense signals from the enterocytes. How this mechanism is carried out is still unknown. Although there is yet not enough evidence to argue against the liver’s role in the regulation of food intake, there are strong indications that the enterocytes are involved. More research within this area will undoubtedly lead to further support for this theory.